The fabrication of TiO2 nanostructures on porous silicon for thermoelectric application - Muhd Ramli Narayanan, Nurhayati (2021)
In the era of globalization, heat is a no doubt to be found in nearly all devices and applications of energy. However, that lost heat is actually representing a substantial portion of energy losses that need to be recovered. The recovery of lost heat is a crucial step in reducing our energy requirements. Therefore, the needs for high-performance thermoelectric (TE) materials to convert heat into electricity and vice versa is become compelling. Nowadays, the leading TE materials are Bi2Te3-based alloys, PbTe, PbSe, SiGe, Mg2X (X = Si, Ge, Sn), skutterudite, and half-Heusler alloys. However, there are some problems arise since most of these rare earth alloy-based TE materials, such as Bi2Te3 and PbTe, suffer from thermal and chemical instabilities. Besides, it is also high toxicity, relatively low availability and high cost. On the other hand, transition metal oxide materials have received attention such as TE materials as they are cost-effective, environmentally friendly, and available over a range of compositions. Titanium Dioxide (TiO2) is among the most widely used transition metal oxides, which takes advantage of its versatility. In this project, a novel and facile method of low temperature hydrothermal method was implemented for the growth of TiO2 nanostructures on porous silicon by using Titanium (IV) Butoxide (TBOT) and Hydrochloric acid (HCL) electrolytes. As a substrate, porous silicon samples were fabricated by electrochemical-etching (ECE) process which helps in providing large internal surface that can induce large absorption of TiO2 nanostructures. Optimization of etching time and current density supplied during the ECE process can alter the morphological properties of the porous silicon sample produced. Next, variation in reaction times during hydrothermal process is also studied since it can affect both the growth pattern and coverage area of TiO2 nanostructures on the porous silicon substrate. Finally, Hall Effect measurement was conducted to calculate the electrical conductivity, carrier concentration and mobility of the TiO2 materials on the porous silicon sample produced. In conclusion, there is a possibility for porous silicon with a high porosity to be a good adhesive template for the growth of TiO2 nanostructures to be contributed as TE materials.